Analysis of the Security Development of Business Entities in the conditions of Artificial Intellectualization of the Global Space - Zybareva, Oksana V. (My University, 2024)
Evaluating the security development of business entities requires compliance with the criteria of complexity and systematicity in terms of taking into account the multi-faceted spectrum of internal functional and process relationships of the security configuration of the enterprise management, which requires the selection of a wide range of the indicators of parametric evaluation. The aim of this article is to justify a methodical approach to assessing the level of economic security of business structures in the conditions of artificial intellectualization of the global space using the method of taxonomic analysis as a tool for assessing the level of economic security. To use the method of taxonomic analysis in the framework of assessing the level of economic security of economic entities in the conditions of artificial intellectualization of the global space, in the article, the authors substantiated a system of analytical parameters describing the key components of ensuring economic security of economic entities in the context of artificial intellectualization processes of economic development. Differentiation of analytical parameters by functional characteristics of influence on the level of economic security, formation of the corresponding intellectual evaluation component was carried out. The proposed methodical approach was tested on the example of PJSC "Southern Mining and Processing Plant". The applied value of the proposed methodical approach lies in the possibility of substantiating the tools of strategic planning of the company's activities in the conditions of intensification of crisis phenomena and the availability of opportunities to overcome them by means of the intellectualized development.
Keywords: Economic Security, Enterprise, Industrial Security, Personnel Security, Financial Security, Intellectual Security